2016
DOI: 10.3311/ppch.8461
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Flow Channel Design and Operating Parameters on Proton Exchange Membrane Fuel Cell Using MATLAB

Abstract: Operating parameters like pressure, temperature, the stoichiometric ratio of reactants, relative humidity and design parameters like rib width to channel width (L:C), the shape of the flow channel and the number of passes on the flow channel are influencing the performance of the Proton Exchange Membrane Fuel Cell (PEMFC IntroductionThe PEMFCs are being developed for commercial applications in the areas of transportation, back-up power and portable power. One of the main advantages is the negligible emission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Thermo-physical properties were constant and the porous GDL, two catalyst layers used in the anode & cathode side and the membrane were an isotropic in nature. The following equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were involved in the model mentioned above.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermo-physical properties were constant and the porous GDL, two catalyst layers used in the anode & cathode side and the membrane were an isotropic in nature. The following equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were involved in the model mentioned above.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The performance of a PEM fuel cell was improved in the study carried out by Lakshminarayanan and Karthikeyan [10]. The authors investigated the combined effect of design and operating parameters of the serpentine and the interdigitated flow channel with 25 cm 2 of active area using the optimization technique and CFD.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the optimum ranges of stoichiometry of fuel and oxidants on anode and cathode leads to the best performance. The performance enhancement of the combined effect of design and operating parameters of serpentine and interdigitated flow channel with 25cm 2 active area of PEM fuel cell with four different parameters using optimization technique and CFD carried out by Lakshminarayanan and Karthikeyan [14]. The results revealed that the peak power density of interdigitated flow channel with landing to channel width (L:C)-1:2 showed better than the serpentine flow channel with L:C-1:2.…”
mentioning
confidence: 94%
“…They concluded that for achieving higher power densities, the ratio of landing width to channel width should be relatively smaller. The performance enhancement of the combined effect of operating and design parameters (operating pressure, temperature and inlet mass flow rate of reactant gases and rib to channel width ratio) of single pass serpentine and interdigitated flow channel with 25 cm 2 active area of PEMFC carried out by Lakshminarayanan and Karthikeyan [12]. The results revealed that the maximum power density of interdigitated flow channel with landing to channel width 1:2 showed better performance than the serpentine flow channel with same design parameter.…”
Section: Introductionmentioning
confidence: 99%